The Influence of the Use of Modules by Tutors on Increasing Student Interest in Learning IPS Courses in Elementary School in Wajo District - Sukarman Sukarman; Rustam Rustam (EduLine: Journal of Education and Learning Innovation, 2023)
The purpose to be achieved in this study, is to determine the magnitude of the influence of the module on increasing student interest in learning in elementary social studies courses in Wajo District. This research is an experimental research by dividing two research groups. The first group was given treatment, while the second group did not receive treatment. The sample in this study were 70 undergraduate students of PGSD Pokjar Disdik Wajo Kab. Wajo, South Sulawesi. The results of the study found that the interest in learning of students who were taught using modules was higher than the interest of students who were taught without using modules. The conclusion is shown from the sub-aspects, namely: (1) attention to the tutor's presentation, (2) interest in the module used, (3) participation in learning activities in class, (4) activity of asking questions about the material to the tutor, (5) activity of answering questions asked by the tutor, and (6) activity of questions asked by friends.